A review of food allergy-related costs with consideration to clinical and demographic factors. Issue 3 (28th June 2023) - Golding, Michael A.; Protudjer, Jennifer L.P.
Abstract : Purpose of review: To provide an overview of the magnitude and sources of food allergy-related costs, with a particular emphasis on the recent literature. We also aim to identify clinical and demographic factors associated with differences in food allergy-related costs. Recent findings: Recent research has expanded upon previous studies by making greater use of administrative health data and other large sample designs to provide more robust estimates of the financial burden of food allergy on individuals and the healthcare system. These studies shed new light on the role of allergic comorbidities in driving costs, and also on the high costs of acute food allergy care. Although research is still largely limited to a small group of high-income countries, new research from Canada and Australia suggests that the high costs of food allergy extend beyond the United States and Europe. Unfortunately, as a result of these costs, newly emerging research also suggests that individuals managing food allergy, may be left at greater risk of food insecurity. Summary: Findings underscore the importance of continued investment in efforts aimed at reducing the frequency and severity of reactions, as well as programs designed towards helping offset individual/household level costs.